1976
DOI: 10.1172/jci108479
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of stimulation of H+ transport by aldosterone in turtle urinary bladder.

Abstract: A B S T R A C T Aldosterone stimulates not only Na4 absorption but also urinary acidification. In this investigation the effects of aldosterone on H4 transport are examined in vitro in turtle bladder, a urinary membrane in which several of the factors controlling H4 transport have been defined. H+ transport was increased in bladder halves exposed to aldosterone compared to control halves. Stimulation of H4 secretion was observed as early as 1 h after addition of aldosterone and occurred before that of Na4 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 16 publications
(19 reference statements)
5
44
0
1
Order By: Relevance
“…Whereas adrenalectomy interferes with net acid excretion, aldosterone has been shown to correct the inability to establish steep urine-to-blood pH gradients (31). Furthermore, aldosterone increases the activity of vacuolar H ϩ -ATPases in rat and rabbit cortical and medullary collecting ducts, and these effects are mimicked in isolated turtle bladder (32). Evidence that this mineralocorticoid is necessary for appropriate urinary acidification is also derived from patients with inborn or acquired aldosterone deficiency syndromes (distal renal tubular acidosis type IV) or in animal models with adrenalectomy or pharmacological blockade of the aldosterone pathway (10,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas adrenalectomy interferes with net acid excretion, aldosterone has been shown to correct the inability to establish steep urine-to-blood pH gradients (31). Furthermore, aldosterone increases the activity of vacuolar H ϩ -ATPases in rat and rabbit cortical and medullary collecting ducts, and these effects are mimicked in isolated turtle bladder (32). Evidence that this mineralocorticoid is necessary for appropriate urinary acidification is also derived from patients with inborn or acquired aldosterone deficiency syndromes (distal renal tubular acidosis type IV) or in animal models with adrenalectomy or pharmacological blockade of the aldosterone pathway (10,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In the collecting tubule, as in the other acidifying segment (the proximal tubule), there are acute and chronic responses to an acid load. Acute responses might include the following: exocytosis of vesicles containing H + ATPases, thereby increasing the number of proton pumps on the surface (1, 2); assembly and disassembly of various subunits; and kinetic effects on the ATPase mediated by cytoplasmic acidification, kinetic activation of soluble adenyl cyclase (3), as well as by hormones such as angiotensin II (4) and aldosterone (5).…”
Section: Introductionmentioning
confidence: 99%
“…was added in 50 ,l of methanol to give a final concentration of 0.5 ,uM. This concentration is half the concentration used by LeFevre (16) in the turtle bladder and has been effective in the stimulation of JH and JNa in our previous study (14). Spironolactone (Sigma Chemical Co.), 17-hydroxy-7a-mercapto-3-oxo-17a-pregn-4-ene-21-carboxylic acid y-lactone 7-acetate, was added to 50 ,ul of methanol to give a final concentration of 50 ,u M. The same volume of methanol was added to the control halves.…”
Section: Methodsmentioning
confidence: 97%
“…Alternatively, aldosterone might stimulate these secretory processes by separate mechanisms. Recent studies have shown that aldosterone can directly stimulate hydrogen secretion in two urinary epithelia; in the bladder ofthe Colombian toad (13) and the bladder of the freshwater turtle, Pseudemys scripta (14). The studies in turtle urinary bladder have further shown that the stimulation of hydrogen secretion precedes that of sodium transport and has different substrate requirements (14).…”
Section: Introductionmentioning
confidence: 99%